KEPEMIMPINAN KEPALA MADRASAH DALAM PENGEMBANGAN LEMBAGA PENDIDIKAN ISLAM DI MA DARUL FAIZIN ASSALAFIYAH MOJOWARNO JOMBANG - A. Arinal Haq; Ahmad Subekti; Muhammad Fahmi Hidayatullah (VICRATINA, 2022)
First class or superior institution, urgency of doing this research is closely related to Madrasah Leaders who are in direct contact with supporting factors, the concept of leadership at MA Darul Faizin Assalafiyah Mojowarno Jombang. The method used by  researcher a qualitative approach. This research refers to primary and secondary data sources, namely, primary data which includes the head of the madrasa, leadership of the head of the madrasa, secondary apparatus and teachers. Interview, documentation, and observation, the method will provide  process according to facts , this research is intended to describe concept of Islamic education in relation to the leadership, quality of the leadership’s head of the madrasa in developing Islamic education institutions in the Aliyah Madrasah Darul Faizin Assalafiyah Catakgayam Mojowarno Jombang, Supporting and Inhibiting Factors of the Head of Madrasah Leadership in the Development of Islamic Educational Institutions, Efforts of the Head of Madrasah Leadership in the Development of Islamic Educational Institutions. This research intends to optimize Islamic Educational Institutions. Concept  research found deficiencies or inhibiting factors, namely facilities and infrastructure, quality of teachers, funding and the minimal role of the community in the importance of Islamic religious education forming aqla 'and not  based on formal education.